Hierarchical nanosheet-based CoMoO4–NiMoO4 nanotubes for applications in asymmetric supercapacitors and the oxygen evolution reaction. Issue 45 (13th October 2015) - Yin, Zhuoxun; Chen, Yujin; Zhao, Yang; Li, Chunyan; Zhu, Chunling; Zhang, Xitian
Abstract : Hierarchical nanosheet-based CoMoO4 –NiMoO4 nanotubes exhibit superior electrochemical properties for applications in asymmetric supercapacitors and the oxygen evolution reaction. Abstract : Hollow structures with hierarchical architecture and multi-composition have attracted extensive interest because of their fascinating physicochemical properties as well as wide applications. Herein we report the designed synthesis of hierarchical nanosheet-based CoMoO4 –NiMoO4 nanotubes by a hydrothermal treatment and a subsequent calcination method. The walls of the hierarchical nanotubes are composed of interconnected NiMoO4 nanosheets and CoMoO4 nanoparticles anchored on the surface of the nanosheets. The diameter of the hollow interior, the thickness of NiMoO4 nanosheets and the diameter of CoMoO4 nanoparticles are around 180 nm, less than 6 nm and 3 nm, respectively, providing the hierarchical nanotubes with a high surface area and a large pore volume. When evaluated as electrodes for pseudocapacitors, the hierarchical nanotubes with an appropriate amount of CoMoO4 show a high specific capacitance of 1079 F g −1 at a current density of 5 A g −1 and excellent stability with 98.4% capacitance retention after 1000 cycles. Furthermore, an asymmetric capacitor, consisting of active carbon and hierarchical nanosheet-based CoMoO4 –NiMoO4 nanotubes as negative and positive electrodes, respectively, delivers an energy density of 33 W h kg −1 at a power density of 375 W kg −1, and 16.3 W h kg −1 even at a high power density of 6000 W kg −1 . The supercapacitive properties are much higher than those of single-phase NiMoO4 nanotubes, and most of the other metal molybdates and metal oxides reported previously. Besides, the hierarchical nanotubes also exhibit much better electrocatalytic activity for the oxygen evolution reaction than single-phase NiMoO4 nanotubes, and most of the other metal molybdates and metal oxides. Our results demonstrate the importance of rational design of complex hollow structures with enhanced properties for a wide range of practical applications.